Analisis Kadar Air, Daya Kembang dan Uji Organoleptik Kerupuk Tape Singkong Kuning dengan Konsentrasi Tape yang Berbeda - Andi Eko Wiyono; Indira Maharani Hidayat; Nur’aini Mardhi Utami; Yusriyyah Vika Rahmadhani; Tiara Dwi Kusuma Putri; Marsa Suci Nurmalasari; Vindha Dhila Wulandari; Shinta Pramudita; Khoirul Umam; Nuril Rohmawati; Viola Risti Agasi (Jurnal Kajian dan Penelitian Umum, 2023)
Tape crackers are one of the innovations in developing cracker products made from tape. Crackers are a type of snack that experiences volume expansion to form a porous product and has a low density during the frying process. The aim of this research was to determine the water content, flowering power and organoleptic properties of crackers made from yellow cassava tape. This research was designed using a Completely Randomized Design (CRD) which was arranged with 1 factor, namely: A1 = Tapioca flour 80 grams + Wheat flour 20 grams + Tape 50 grams; A2 = Tapioca flour 80 grams + Wheat flour 20 grams + Tape 75 grams; A3 = Tapioca flour 80 grams + Wheat flour 20 grams + Tape 100 grams. The results of the organoleptic test were data analysis using ANOVA (analysis of variance) and Duncan's further test was carried out at α = 5%. The panelists' assessment or organoleptic test of the combination of tapioca flour, wheat flour and tape gave no real influence on the color and aroma and had a real influence on the taste and texture of the tape crackers.